Exercise Alleviates the Apolipoprotein A5-Toll-Like Receptor 4 Axis Impairment in Mice With High-Fat Diet-Induced Non-alcoholic Steatohepatitis - Yu, Yang; Yu, Lina; Cheng, Nuo; Liu, Xiaoguang; Fang, Chunlu; Liu, Shujing; Zhu, Lin (Frontiers in Physiology, 2021)
Background: Apolipoprotein A5 (ApoA5), an important modulator of plasma and hepatic triglyceride metabolism, has been found to be downregulated by metformin to improve non-alcoholic fatty liver disease. Meanwhile, exercise has been recommended as a therapeutic strategy for non-alcoholic steatohepatitis (NASH). However, no study has yet determined whether exercise affects hepatic ApoA5 expression or the inhibition of ApoA5 to toll-like receptor 4 (TLR4). We herein examined the effects of exercise on hepatic ApoA5 expression and the relevance of ApoA5 and TLR4-mediated pathway in mice with high-fat diet (HFD)-induced NASH. Methods: Male C57BL/6J mice were built NASH model with high-fat diet for 12 weeks, and following mice were subjected to exercise for 12 weeks on a treadmill. Microscopy and enzyme-linked immunosorbent assay were used to measure histological analysis of liver and hepatic lipids, respectively. Quantitative real-time PCR and western blot were used to determined mRNA and protein levels of ApoA5 and TLR4-mediated nuclear factor kappa B (NF-κB) pathway components, respectively. ApoA5 overexpression plasmids transfected into mice to investigate the relevance of ApoA5 and TLR4. Results: 12 weeks of exercise remarkably alleviated HFD-induced hepatic lipid accumulation, inflammation, and fibrosis, as well as reduced serum lipopolysaccharide (LPS), hepatic TLR4, myeloid differentiation factor 88 (MyD88), and NF-κBp65 expression. Importantly, exercise did not reduce ApoA5 expression but instead enhanced its ability to suppress TLR4-mediated NF-κB pathway components by decreasing circulating LPS in our experiments involving transfection of ApoA5 overexpression plasmids and LPS interventions. Conclusion: The results demonstrated that exercise improved HFD-induced NASH by triggering the inhibitory effects of ApoA5 on the TLR4-mediated NF-κB pathway.